AN EXPLORATION OF COMORBID SYMPTOMS AND CLINICAL CORRELATES OF CLINICALLY SIGNIFICANT HOARDING SYMPTOMS. Issue 1 (4th December 2012) - Hall, Brian J.; Tolin, David F.; Frost, Randy O.; Steketee, Gail
<x xml:space="preserve">Abstract</x> Background Hoarding disorder (HD) is currently being considered for inclusion in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM‐5), yet remains poorly understood. Consensus is building that hoarding may constitute a separate disorder, although comorbidity remains high and complicates the diagnostic picture. The purpose of this investigation was to explore patterns of comorbidity among people who engage in hoarding behavior in order to better understand its clinical presentation and phenomenology. Methods Data were collected from a large internet sample (N = 363) of people who self‐identified as having hoarding problems, met criteria for clinically significant hoarding, and completed all measures for this study. Participants self‐reported their symptoms of disorders commonly co‐occurring with hoarding (obsessive‐compulsive disorder [OCD], depression, and attention deficit hyperactivity disorder [ADHD]), along with other clinical problems. Results Latent class analysis results indicated that the participants were grouped into three classes: "non‐comorbid" hoarding (42%), hoarding with depression (42%), and hoarding with depression and inattention (16%). Conclusions Depression symptoms were the most commonly co‐occurring symptom in this sample. Contrary to previous theory relating to hoarding etiology, OCD symptoms were not significantly co‐occurring and a large percentage of the study participants were free from comorbid symptoms of OCD, depression, and ADHD. This suggests that HD is not primarily the consequence of other psychiatric conditions. Implications for DSM‐5, clinical treatment, and future research directions are discussed.